Revised Bloom's taxonomy and major theories and frameworks that influence the teaching, learning, and assessment of mathematics: a comparison. Issue 6 (18th August 2019) - Radmehr, Farzad; Drake, Michael
ABSTRACT: This paper compares Revised Bloom's Taxonomy (RBT) and some of the major theories and frameworks that influence the teaching, learning, and assessment of mathematics. This comparison has been made to help students and researchers make decisions about which of the available theories and frameworks might best suit their study. The comparison identifies that RBT has greater potential for analysing the teaching, learning, and assessment of mathematics than many other theories and frameworks because of its broad approach. While other theories and frameworks can be aligned to elements of RBT, they tend to overlook other elements. In particular, the strength of RBT comes from its two dimensional structure, its inclusion of metacognitive knowledge, and its rejection of strict hierarchy.